PENGEMBANGAN MULTIMEDIA BERBASIS INTERAKTIF UNTUK PENDIDIKAN KESEHATAN DAN NUTRISI ANAK DI KOTA PARI KECAMATAN PANTAI CERMIN KABUPATEN SERDANG BEDAGAI - Rozana, Salma; Widya, Rika; Tasril, Virdyra (Seminar Nasional Sosial Sains dan Teknologi Halal, 2022)
This research was conducted moving from the problems found in schools, namely learning about AUD health which makes the learning process monotonous. The uncertain situation during online learning makes teachers need learning media that can be used for online and offline learning. This study aims to describe the design and determine the validity of interactive multimedia-based media on aspects of early childhood health. This type of research is research and development using the ADDIE development model. The subjects in this study were 5 including 1 learning content expert, 1 learning design expert and learning media expert, and 3 children in group B in the individual test. The data in this study were collected using a questionnaire method which was then analyzed using quantitative descriptive analysis techniques. Validity test according to learning content experts, learning design experts and learning media experts with good qualifications and trials with very good qualifications. So it can be stated that this interactive multimedia-based media is suitable for use in early childhood health aspects. The implication of this research is that this media product can be a solution to existing problems, which can be used in online and offline learning and can make learning more varied.